Adjacent Segment Disease Associated with Klippel-Feil Syndrome: A New Classification System with Corresponding Therapeutic Options - Murat, Yilmaz; Ersin, Ikizoglu; Mert, Arslan; Serhat, R. Erbayraktar; Kemal, Yucesoy (Journal of Current Scientific Research, 2021)
Background Klippel-Feil Syndrome (KFS) is described as the clinical triad of short neck, low posterior hairline, and limitation of neck mobility. Objective Topresent our clinical experience with KFS patients who also had adjacent segment disease (ASD) and to propose a novel classification system for these patients. Methods This retrospective study was performed in the neurosurgery department of our tertiary care center. Data were gathered using the medical records of 22 KFS patients (10 males, 12 females) with ASD. Diagnosis was confirmed with imaging modalities including X-ray, computerized tomography, and magnetic resonance imaging. Clinical and radiological findings as well as therapeutic outcomes were noted. Results The average age of our series was 56.09 (range: 41 to 67) years. The operative technique was selected as for our novel “Yilmaz-Yucesoy Classification System”. Accordingly, one patient (4.54 %) received non-surgical treatment (Yilmaz-Yucesoy Grade 1), six cases (27.27 %) underwent anterior cervical arthroplasty, seven patients (31.81 %) underwent anterior cervical discectomy or corpectomy and fusion with cervical cage and plate (Yilmaz-Yucesoy Grade 3). Eight patients (36.36 %) with cervical spinal instability had anterior cervical discectomy or corpectomy and fusion with cervical cage and plate (Yilmaz-Yucesoy Grade 4). No mortality or remarkable complications were detected. Conclusion Appropriate and timely recognition and classification of patients with KFS and ASD based on our newly proposed “Yilmaz-Yucesoy Classification System” yielded promising treatment outcomes. However, further prospective, randomized, controlled trials are warranted on larger series to validate our preliminary results.
Keywords: Klippel-Feil Syndrome; spinal fusion; adjacent segment disease; classification; treatment.